(3HdhZ GdeQGe ef SjQI GHf gTGe hGdQhV GdCfa hGdCYdGes - (3CHh HcQ Hf Ydj Hf YHO Gddg GdMehj GdCRQGQj, Jbj GdOjf GHf MLI,J (B837 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi ef YdjfG HHdhZ GdeQGe ef SjQI fHjfG Ydjg CaVd GdUdGI hGdSdGe hGdTcQ ddg GdPi fRgfG ajgG HGdQhV GdCfa s
(3BNQgG (B:s
(3Je GdLRA GdChd ef HdhZ GdeQGeq s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydi dhMI GdYfhGf JedcGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B67s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs